The Foreclosure Crisis, the American Dream, and Minority Households in the United States: A Descriptive Profile - Aguirre, Adalberto (Social justice, 2013)
The article discusses effects of the home mortgage foreclosure crisis on ethnic and racial minority households in the U.S. Topics include analysis of neighborhood social conditions and social disorganization, the loss of equity wealth of minority householders, and persistence of economic inequality and racial privilege.